Vennesla Bibliotek, konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2023)
Vennesla library was completed in 2011 after winning the competition for a new library and community center. The goal was to draw more people into the library and to become an inviting place for the public. The project infills the space between an existing community house and a learning center and seeks to become an extension to the main city square. The building is mainly built in wood and the structure consists of 27 ribs made of prefabricated glue-laminated timber. The ribs span like arches over the main level and form the geometry of the roof. These hybrid structures contain technical devices and has integrated seating and bookshelves.
Vennesla Library, concept model
Keywords: Nordic architecture; Nordisk arkitektur; Female architects; Kvinnliga arkitekter; Vennesla library; Vennesla bibliotek; Library; Bibliotek